On a Very Basic Behavior in Science: Importance and Issues with Quotations - Bauer, Michael (Pharmacopsychiatry, 2020)
This journal, founded in 1968, not only has a publication history of more than 5 decades but also stands for a distinct scientific focus in psychiatric pharmacology or psychopharmacology: the research on medication treatments for mental disorders. At some point, it is worth taking a broader look at what we are doing in psychiatry or in medicine in general. That is why, in this issue, we are publishing a study by Christopher Baethge 1 that typically may not fit into the scope of Pharmacopsychiatry. As a psychiatrist and an editor, Baethge carried out an investigation in an underresearched area: the accuracy and significance of citations in psychiatric journals.